Exhaust Flue Gas Concentration of Engines Running on Ethanol, Gasoline and Bio-oil - a Theoretical Estimate - Júnior, Moilton Ribeiro Franco; Rocha, Nattácia Rodrigues de Araújo Felipe; Pereira, Warley Augusto (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
The creation of new technologies over the last 100 years has improved the quality of human life, but the necessary chemical and industrial transformations have caused significant changes in the environment. The production of new inputs depends on the chemical processes employed and, as a consequence, must be in line with water and air treatments that are undoubtedly undermined by world technological development. Thus, the principles of physics and chemistry apply to the prediction and understanding of the release of gaseous pollutants into the environment, which come from the burning of fuels in automobiles. It also discusses the influence of aspects related to the air content fed to the engine, as well as the effect of temperature and pressure on the concentration of these pollutants.